HUBUNGAN LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA MASA PANDEMIK COVID-19 (STUDI KASUS MATAHARI DEPARTMEN STORE, METROPOLITAN MALL CILEUNGSI) - sahara, sahara; Suzzana Josephine L. Tobing; Desideria Regina (Buletin Ekonomi, 2024)
Work environments and work motivations are issues that need attention in a company. The work environments and work motivations that is lacking in the company will be related to employee performances and will result in employees being less enthusiastic and will affect employee performances, which will result in a decrease in employee performances. However, if the work environments and work motivations are good, it will have a good effect on employee performances. The purpose and focus of these studies are to analyze whether or not there is a relationships between the work environments and employee performances, and to analyze whether or not there is a relationships between work motivations and employee performances at Matahari Departmen Store Metropolitan Mall Cileungsi. data collections were carry out by distribute questionnaire to 54 respondents using SPSS 27 Version data processing assistance. The result of these studies indicating that (1) there is a relationships between the work environments and employee performances at Matahari Department Store Metropolitan Mall Cileungsi, the rank spearman correlations coefficient of 0.338 is obtained and a significancy result of 0.000 is less than 0.05, so the results of this calculation can be concluding that there is a significancy relationships between work environments variable on employee performances. (2) there is a relationships between work motivations and employee performances at the Matahari Department Store Metropolitan Mall Cileungsi and a Spearman rank correlations coefficient of 0.639 is obtained and a significance result of 0.000 is less than 0.05, so the result of these calculations may be concluding that there is a significancy relationships between variables work motivations on the performances of Matahari Department Store Metropolitan Mall Cileungsi employees. Keywords: Work Environment, Work Motivation, Employee Performance